“Many are the plans”: An analysis of goals described by youth ministry leaders - Greenway, Tyler S. (Archive for the psychology of religion, 2021)
This article examines the content and appraisals of youth ministry leader goals. Responses to an open-ended survey question by 378 leaders primarily working in the United States who held significant responsibility for the discipleship of high school-aged young people in their ministries were coded, resulting in 29 categories of goals. Participants named goals associated with service, relationships in general, relationships with God, biblical/gospel knowledge, and discipleship most frequently. Leaders rated each goal according to factors that contribute to goal achievement and well-being. Appraisals of goal difficulty (“this goal involves challenge”), clarity (“this goal is well-defined”), satisfaction with progress (“this goal is moving forward satisfactorily”), and support (“other leaders and congregants encourage the pursuit of this goal”) varied significantly across goals. Of note, participants rated discipleship and partnerships with parents/families as progressing the least satisfactorily and as some of the most difficult goals. By contrast, participants rated service goals as some of the least difficult and most clear. The content and appraisals of these goals bear implications for both the psychological study of goals and strivings and for ministry practice.